Regulatory Effect of Pyroptosis Related Genes Expression in Adipose Tissue of Aging Rats by Long-Time Weight-Bearing Running - GONG Lijing; TANG Shuning; YANG Luyao; SU Hao; NI Zhen; FU Pengyu (康复学报)
ObjectiveTo explore the effect of long-time weight-bearing running on the expression of NLRP3-mediated pyroptosis-related genes and proteins in adipose tissue of aging rats.MethodsA total of thirty-five 8-month-old SD rats were randomly divided into three groups: the baseline group (the samples were taken after 3 days of adaptive feeding); the control group (fed for 32 weeks, without exercise); and the resistance training group (fed for 32 weeks, with 3 times/week of weight-bearing running training), with 10 mice per group (5 mice died). After the intervention, the body weight, body composition, perirenal and subcutaneous adipose tissue (p/sWAT) wet weight and blood lipids were measured; the morphology of adipocytes were observed by HE staining, and the cross-sectional area (CSA) of adipocyte was calculated; the relative expression level of ASC, NF-κB, IL-1β, GSDMD, NLRP3 and Caspase1 mRNA were tested by RT-PCR; the immunopositive expression of ASC, IL-1β, GSDMD, NLRP3 and Caspase1 were observed by Immunofluorescence, and the integral optical density (IOD) value was calculated.Results(1) After the intervention, the body weight of rats in the control group was higher than that in the baseline group, and the body weight of rats in the resistance training group was lower than that in the control group (P<0.05); the body fat percentage of the resistance training group was lower than those in the control and baseline groups (P<0.05), respectively; the muscle content percentage of rats in the control group was lower than that in the baseline group, and the muscle content percentage of rats in the resistance training group was higher than that in the control group (P<0.05). (2) After 32 weeks of intervention, the plasma levels of TG, TC, HDL-C, LDL-C and FFA of rats in the control group were higher than those in the baseline group, and the levels of TG and FFA of rats in the resistance training group were lower than those in the control group (P<0.05). (3) After 32 weeks of intervention, the wet weight percentages of pWAT and sWAT of rats in the control group were higher than those in the baseline group; the wet weight percentage of pWAT of rats in the resistance training group was lower than those in both the control and baseline groups, and the wet weight percentage of sWAT of rats was lower than that in the control group (P<0.05); the CSA of adipocyte of sWAT and pWAT of rats in the resistance training group was smaller than those in the control and baseline groups (P<0.05), respectively. (4) After 32 weeks of intervention, the relative expression levels of ASC, NF-κB, IL-1β, NLRP3 and Caspase1 mRNA in pWAT of rats in the control group were higher than those in the baseline group, and the relative expression levels of NF-κB and IL-1β mRNA in sWAT were higher than those in the baseline group (P<0.05). The relative expression levels of ASC, NF-κB, IL-1β and NLRP3 mRNA in pWAT of rats in the resistance training group were lower than those in the control group (P<0.05), and the relative expression levels of NF-κB and NLRP3 mRNA were lower than those in the baseline group, and the relative expression level of Caspase1 mRNA was higher than that in the baseline group (P<0.05).The relative expression levels of NF-κB and IL-1β mRNA in sWAT of rats in the resistance group were lower than those in the control group, and the relative expression levels of ASC, NF-κB and Caspase1 mRNA were higher than those in the baseline group (P<0.05). (5) After 32 weeks of intervention, the IOD values of NLRP3, Caspase1, GSDMD and IL-1β in pWAT of rats in the control group were higher than those in the baseline group (P<0.05). The IOD values of Caspase1, GSDMD and IL-1β in the resistance training group were higher than those in the baseline group (P<0.05), and the IOD values of NLRP3, Caspase1 and GSDMD were all lower than those in the control group (P<0.05). The IOD values of NLRP3, Caspase1 and IL-1β in sWAT of rats in the control group were higher than those in the baseline group (P<0.05), and the IOD values of ASC, NLRP3, Caspase1, GSDMD and IL-1β in the resistance training group were lower than those in the control group (P<0.05).ConclusionThe body fat percentage and blood lipid levels in aging rats are reduced by weight-bearing running training, via inhibiting the expression of NLRP3-mediated pyroptosis-related genes and protein of adipose tissue.